The Effect of Animated Videos in a Flipped Classroom on Students’ Recount Text Reading Comprehension - Rishka Wulan Setiayani; Patuan Raja; Flora (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study investigated the effect of animated videos in a flipped classroom on eighth-grade students’ reading comprehension of recount texts in Metro City, Lampung. A purposive sampling technique was applied to 52 students. The study employed a quasi-experimental design that consisted of a pre-test and post-test. Pre-test results indicated that the control and experimental groups were relatively homogeneous, with mean scores of 45.69 and 48.92, respectively. Post-test results showed that the experimental group achieved a higher mean score of 76.00 than the control group, 59.54, with a 2-tailed significance value of .000 (p < .05), demonstrating a significant difference in reading comprehension achievement. Students in the experimental group showed greater improvement across all reading comprehension aspects, indicating that animated videos effectively support learning. The findings suggest that integrating animated videos into flipped classrooms can enhance students’ engagement and comprehension skills, offering teachers a practical strategy to improve reading outcomes in language learning.